A Dual Approach with Organoid and CRISPR Screening Reveals ERCC6 as a Determinant of Cisplatin Resistance in Osteosarcoma - Ruiling Xu; Sai Zhu; Wenchao Zhang; Haodong Xu; Chao Tu; Honghui Wang; Lu Wang; Na He; Tang Liu; Xiaoning Guo; Xiaolei Ren; Zhihong Li (Advanced Science, 2025)
Abstract Osteosarcoma (OS), the most prevalent primary bone malignancy in adolescents, is typically treated with cisplatin‐based chemotherapy. However, the development of cisplatin resistance often leads to relapse or metastasis, significantly impairing therapeutic efficacy. To tackle this issue, patient‐derived osteosarcoma organoids (OSOs) is established that accurately reflect the cellular composition and heterogeneity of the original tumors, as validated by single‐cell RNA sequencing, bulk RNA sequencing, and histopathology analysis. Cisplatin resistance is successfully induced in these OSOs, creating a clinically relevant model for investigating chemoresistance. Utilizing RNA sequencing in cisplatin‐resistance OSOs and CRISPR screening in OS cell line, ERCC6 is identified as a pivotal regulator of cisplatin resistance. Knockdown of ERCC6 markedly enhanced cisplatin sensitivity in vitro and in vivo. Mechanistically, ERCC6 interacts with HNRNPM, influencing the PI3K/AKT signaling pathway and alternative splicing of pre‐mRNA for BAX. Notably, the knockdown of ERCC6 and HNRNPM increased expression of full‐length BAX and reduced skipping of exon 2, thus promoting apoptosis. This exon skipping in BAX results in a frameshift and introduces a premature stop codon (TGA) within the BH3 domain. These findings underscore the utility of OSOs in elucidating resistance mechanisms and highlight ERCC6 and HNRNPM as potential therapeutic targets.